The impact of soybean futures and crude oil futures on palm oil indexes: Evidence from bounds test of level relationship and causality analysis - Izaan Jamil; Mori Kogid; Thien Sang Lim; Jaratin Lily (Economies, 2022)
This paper investigates the impact of soybean and crude oil futures on palm oil indexes by utilising monthly data from three palm oil indexes listed in Bursa Malaysia, i.e., the Asian palm index, Malaysian palm index, and Plantation index, spanning from January 2010 to June 2020. The impacts were analysed using the Autoregressive Distributed Lag (ARDL) bounds test approach and causality test. The statistical findings revealed that the Asian palm index has a long-run relationship with crude oil futures and crude palm oil, and a short-run relationship with soybean futures, crude oil futures, and crude palm oil. On the other hand, the Malaysian palm index has a short-run relationship with soybean futures and crude palm oil, whereas the Plantation index has a short-run relationship with crude oil futures, crude palm oil, and exchange rate. For the long-run strategy, this study recommends close monitoring of crude oil futures. Meanwhile, the short-run strategy requires close monitoring of the crude oil and soybean futures. Eventually, the empirical findings proposed that interested parties such as fund managers, investors, and traders should pay attention to crude oil and soybean futures to mitigate risk and diversify their portfolios with greater emphasis on crude oil futures.
Keywords: 330; ARDL; crude oil futures; palm oil indexes; soybean futures